Influence of pipe materials on in-building disinfection of P. aeruginosa and A. baumannii in simulated hot water plumbing - Abraham Cullom; Mattheu Storme Spencer; Myra D. Williams; Joseph O. Falkinham, III; Amy Pruden; Marc A. Edwards (Water Research X, 2023)
A framework is needed to account for interactive effects of plumbing materials and disinfectants on opportunistic pathogens (OPs) in building water systems. Here we evaluated free chlorine, monochloramine, chlorine dioxide, and copper-silver ionization (CSI) for controlling Pseudomonas aeruginosa and Acinetobacter baumannii as two representative OPs that colonize hot water plumbing, in tests using polyvinylchloride (PVC), copper-PVC, and iron-PVC convectively-mixed pipe reactors (CMPRs). Pipe materials vulnerable to corrosion (i.e., iron and copper) altered the pH, dissolved oxygen, and disinfectant levels in a manner that influenced growth trends of the two OPs and total bacteria. P. aeruginosa grew well in PVC CMPRs, poorly in iron-PVC CMPRs, and was best controlled by CSI disinfection, whereas A. baumannii showed the opposite trend for pipe material and was better controlled by chlorine and chlorine dioxide. Various scenarios were identified in which pipe material and disinfectant can interact to either hinder or accelerate growth of OPs, illustrating the difficulties of controlling OPs in portions of plumbing systems experiencing warm, stagnant water.